Model amalan pentaksiran formatif dalam kalangan guru-guru kemahiran hidup bersepadu - Hussin, Ahmad Zaidi (2019)
Formative assessment is an assessment adopted in the School-Based Assessment (SBA) to assess student learning in the classroom. However, since SBA was first introduced in 2011, the issue of teachers' practices in the formative assessments often received attention from various quarters whether teachers or researchers. This is because previous studies show that teachers still fail to meet the standards set by policymakers. Therefore, this research is focused on formative assessment in SBA to test the model of assessment practices among Integrated Living Skill (ILS) teachers in Peninsular Malaysia. This study employed a quantitative study design by surveying through a questionnaire distributed to 300 secondary schools in 12 states from Peninsular Malaysia. A total of 537 ILS teachers were involved in this study, while the data collected were analyzed using descriptive and inferential analysis. The findings showed that the level of practice, knowledge, and skill were at a high level, while attitude, subjective norm, perceived behavioral control, and intention were positively indicating of teachers' readiness to implement formative assessment. The proposed model of the study meets Partial Least Square-Structural Equation Modeling (PLS-SEM) requirements and accepts seven out of eight alternative hypotheses constructed. Teachers also claimed that time constraints are a major challenge in implementing formative assessment practices and they suggested that intensive courses should be held from time to time. The implication of this study is to enable assists the Ministry of Education (MOE) in identifying factors that influence the practice of formative assessment among teachers and the design of the system of the existing will be upgraded.